2020
DOI: 10.1364/oe.386604
|View full text |Cite
|
Sign up to set email alerts
|

MHz-repetition-rate, sub-mW, multi-octave THz wave generation in HMQ-TMS

Abstract: We demonstrate the first megahertz (MHz) repetition-rate, broadband terahertz (THz) source based on optical rectification in the organic crystal HMQ-TMS driven by a femtosecond Yb:fibre laser. Pumping at 1035 nm with 30 fs pulses, we achieve few-cycle THz emission with a smooth multi-octave spectrum that extends up to 6 THz at-30 dB, with conversion efficiencies reaching 10 −4 and an average output power of up to 0.38 mW. We assess the thermal damage limit of the crystal and conclude a maximum fluence of ∼1.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This high optical‐to‐THz conversion efficiency under near‐infrared pumping around 1100 nm is technologically meaningful because diverse high‐power femtosecond laser sources of this wavelength are commercially available or are being developed. [ 16,17 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This high optical‐to‐THz conversion efficiency under near‐infrared pumping around 1100 nm is technologically meaningful because diverse high‐power femtosecond laser sources of this wavelength are commercially available or are being developed. [ 16,17 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] Most currently available benchmark nonlinear organic crystals provide high optical‐to‐THz conversion efficiency under optical pumping in the infrared region of 1300‒1500 nm; [ 1–3,9,10 ] however, at near‐infrared wavelengths of around (and below) 1100 nm, they exhibit inferior phase matching compared to that achieved at longer wavelengths. [ 15,16 ] Note that the ability to pump around 1100 nm is very promising owing to the technological importance of this wavelength, where diverse high‐power femtosecond laser sources at or around this wavelength have been developed, including the recent development of compact high‐power lasers such as Yb:fiber lasers and thin‐disk lasers. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3a,b shows the coherence length for the conventional inorganic NLO semiconducting crystal GaP, which indicates the best velocity matching close to the pump wavelength of 1000 nm, and for one of the benchmark organic crystals HMQ-TMS, respectively. [111] It can be clearly observed that the phase matching can be achieved in a much broader THz spectral range for HMQ-TMS; moreover, the optimal pump wavelength range for the use of HMQ-TMS also extends over a large portion of the infrared wavelengths ranging from 1000 nm to beyond 1600 nm. Approximate phase-matching ranges for the HMQ-TMS crystal as a sample are also presented with gray horizontal lines in Figure 2.…”
Section: Phase Matchingmentioning
confidence: 98%
“…The generated THz amplitude |E THz (ω,λ)| shown in Figure 3c,d correlates well to the coherence length with an additional advantage compared to that of GaP owing to the larger second-order optical susceptibility χ (2) . [111] At a pump wavelength of about 1035 nm, a tenfold increase in the electric field and almost double the THz bandwidth for HMQ-TMS when compared to GaP has been demonstrated, [111] even though this pump wavelength is at the lower edge of the phase-matching range for HMQ-TMS.…”
Section: Phase Matchingmentioning
confidence: 99%